Formation of a New Middle Class as a Result of Stolypin's Reforms in 1906-1911 - Turenko, Polina; Szobi, Pavel, 1983-; Johnson, Zdenka, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The thesis features development and implementation of the agrarian reforms process in the economic and socio-legal context, directed on formation of peasant owners middle class, are analyzed. General approaches to solution of the Russian Empire agrarian and peasant questions are reviewed. Problems of private ownership features in the Russian Empire and influence of communities on economic activity, spiritual traditions, law commitments and life of the Russian peasantry are investigated. Economic and social-legal position of the peasantry before Peter Stolypin reforms are esteemed. Using historiographical, comparative and statistical methods there are introduced key figures that characterize state of the economy and social progress in the peasantry situation. The reforms resulted in rapid agricultural production growth, the internal market expansion, agricultural products export increase. However, the main achievement of the reforms, in my opinion, is inclusion of the Russian peasantry of the early twentieth century into land-market and economic market-capitalist relations, that have served as the basis for a middle class formation in the Russian Empire.
Vedoucí práce: Pavel Szobi
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses